2012
DOI: 10.1080/08905436.2011.645939
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of the Aroma of Pea (Pisum sativum) Protein Extracts by Lactic Acid Fermentation

Abstract: The formation of a green or beany off-flavor during storage of legume protein extracts limits their application in foods. Pea protein extracts were submitted to lactic acid fermentations to improve the flavor by either reducing off-flavor formation or by masking undesirable green notes. The aroma profiles of untreated pea protein extract (PPE) and fermented pea protein extract (PPEF) were compared to each other and to a commercial whey protein as a benchmark. Kinetic measurements of n-hexanal and n-hexanol for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
92
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(100 citation statements)
references
References 37 publications
7
92
0
1
Order By: Relevance
“…Although the fermented extract (LPEF) was not free of off‐flavors, the aroma profile was significantly modified by the fermentation process, and the off‐flavors were reduced or masked by newly formed compounds when compared with the LPE. Similar results were obtained by lactic acid fermentation of pea protein (Schindler et al 2012).…”
Section: Technologies To Remove or Modify Off‐flavor In Pulsessupporting
confidence: 84%
See 2 more Smart Citations
“…Although the fermented extract (LPEF) was not free of off‐flavors, the aroma profile was significantly modified by the fermentation process, and the off‐flavors were reduced or masked by newly formed compounds when compared with the LPE. Similar results were obtained by lactic acid fermentation of pea protein (Schindler et al 2012).…”
Section: Technologies To Remove or Modify Off‐flavor In Pulsessupporting
confidence: 84%
“…Another method used for masking off‐flavors is fermentation. As mentioned earlier, fermentation of pea protein extracts led to the formation of, for example, 2,3‐octanedione, 2‐nonanone, 3‐octen‐2‐one, 2,4‐heptadienal, 2‐nonenal, 2‐undecanone, 2‐octen‐1‐ol, 2,4‐nonadienal, and 1‐decanol (Schindler et al 2012), which could be potentially responsible for masking off‐flavors in pea protein extracts.…”
Section: Technologies For Masking Off‐flavors In Pulsesmentioning
confidence: 89%
See 1 more Smart Citation
“…by LAB during fermentation (Schindler et al, 2012). The initial population of LAB in raw beans was very low (1.01 CFU/ml) and it increased significantly during NF, reaching counts of 8.8 log CFU/ ml after 48 h, which remained almost constant to the end of the fermentation (Table 1).…”
Section: Evolution Of Ph and Microbial Growth During Fermentationmentioning
confidence: 95%
“…In addition, taste perceptions of bitter, salty, and astringent were identified in the taste pattern [5]. This characteristic aroma profile makes lupin proteins less suitable for some food applications as, for example, plain non-dairy based products.The lactic fermentation of legume proteins might be a promising approach to influence the sensory profile of these ingredients as various studies have shown that lactic fermentation of plant proteins results in a reduction or masking of off-flavors in legumes [6,7]. The influence of the fermentation on the aroma profile of the plant proteins strongly depends on the microorganisms used [6][7][8].…”
mentioning
confidence: 99%